Pengembangan Aplikasi Klinik Berbasis Web Untuk Pengelolaan Rekam Medis Menggunakan Metode Agile - Azriel Fachrul Rezy; Mulia Yuga Utama; Noval Rizky Ramadhan (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Doxscien Clinic is a clinic that provides medical health information service facilities and online consultation services. Data on patient medical records at the Doxscien Clinic is currently still being done manually. There are many problems that often occur due to the recording of medical records which is done by the method of recording in the medical record ledger, resulting in human error. The purpose of this research is to build a software system that can manage online, web-based consultation data which is expected to help Doxscien Clinic employees to process consultation data, drug and disease information data. The development method used is agile system design and UML (Unit Modeling Language). So that this research is not subjective, the authors also use research methods in the form of observation, literature review, documentation and analysis of the results of interviews at the Doxscien Clinic. This system was created to be able to assist admins in managing patient consultation data, drug data, doctor data, and disease data. This system has advantages over the currently running system, namely the admin can input data into the system as well as system security using a username and password.